Design and implement the engine control system of Toyota Camry 2AR-FE and fault creation system using IoT technology - Nguyen, Kim; Le, Khanh Tan (Journal of Technical Education Science, 2019)
Currently, in Vietnam, there are many types of engine control system models, but they are only implemented on old generation of electronic fuel injection engines. Which these models, the teaching and learning of students have faced many difficulties. Therefore, in order to meet the current training for industrial needs, the research team has designed and implemented the model of Toyota Camry 2AR-FE engine control system in combination with IoT technology along with data acquisition, fault simulation system to better serve for training and skills testing. The finished product provides learners with the Toyota 2AR-FE engine a model with all sensors, actuators, central controllers, IoT applications in fault simulation, the data acquisition through LabVIEW software, the interface of Techstream diagnostic through OBD II connector. Thereby, learners are able to approach to practical exercises and research quickly.